Validity of bag urine culture for predicting urinary tract infections in febrile infants: a paired comparison of urine collection methods - Geun-A Kim; Ja-Wook Koo (Korean Pediatric Society, 2015)
PurposeCatheter urine (CATH-U) and suprapubic aspiration (SPA) are reliable urine collection methods for confirming urinary tract infections (UTI) in infants. However, noninvasive and easily accessible collecting bag urine (CBU) is widely used, despite its high contamination rate. This study investigated the validity of CBU cultures for diagnosing UTIs, using CATH-U culture results as the gold standard.MethodsWe retrospectively analyzed 210 infants, 2- to 24-month-old, who presented to a tertiary care hospital's pediatrics department between September 2008 and August 2013. We reviewed the results of CBU and CATH-U cultures from the same infants.ResultsCBU results, relative to CATH-U culture results (≥104 colony-forming units [CFU]/mL) were widely variable, ranging from no growth to ≥105 CFU/mL. A CBU cutoff value of ≥105 CFU/mL resulted in false-positive and false-negative rates of 18% and 24%, respectively. The probability of a UTI increased when the CBU bacterial count was ≥105/mL for all infants, both uncircumcised male infants and female infants (likelihood ratios [LRs], 4.16, 4.11, and 4.11, respectively). UTIs could not be excluded for female infants with a CBU bacterial density of 104-105 (LR, 1.40). The LRs for predicting UTIs based on a positive dipstick test and a positive urinalysis were 4.19 and 3.11, respectively.ConclusionThe validity of obtaining urine sample from a sterile bag remains questionable. Inconclusive culture results from CBU should be confirmed with a more reliable method.